CUSTOMER SATISFACTION WITH GOODS DELIVERY SERVICES: THE ROLE OF COURIERS, DELIVERY LOCATIONS, DELIVERY TIME, AND COMPLAINT SERVICE AVAILABILITY IN ONLINE SHOPPING APPLICATIONS - Hendra Jonathan Sibarani; Elizabet Haloho; Fitria Halim; Nora Anisa Sinulingga (PT. ZILLZELL MEDIA PRIMA, 2026)
This study investigates the influence of key factors in delivery services such as courier performance, delivery location, delivery time, and availability of complaint services on customer satisfaction in the context of online shopping applications. Using a quantitative approach and data collected from 300 valid responses in Medan were collected using purposive sampling, this study utilised PLS-SEM through SmartPLS to test the proposed model. The results show that all four factors have a significant and positive impact on customer satisfaction, with delivery time showing the strongest influence. On the other hand, the existence of an easily accessible and responsive complaint system strengthens consumers' trust in e-commerce platforms. Implications for e-commerce platforms and logistics providers are also discussed in this study, thus providing a clear understanding of the performance of e-commerce platforms in Indonesia. In addition, this study also makes a practical contribution by suggesting that e-commerce companies should focus more on improving delivery efficiency and post-purchase service, as well as building a proactive customer complaint system. Academically, the results of this study add to the literature in the field of logistics management and customer satisfaction in the digital era, and open up room for further research that can explore additional factors such as shipping costs, item security, and app user experience.